The first endoscopic resection of a colonic granular cell tumor in a child - Basak Erginel; Melih Akin; Abdullah Yildiz; Canan Alatas Alkim; Canan Tanik; Cetin Ali Karadag; Nihat Sever; Meltem Tokel; Ali İhsan Dokucu (Elsevier, 2016)
Granular cell tumors (GCTs) are rare, generally benign, soft tissue tumors characterized by large, granular, periodic acid-Schiff (PAS) positive eosinophilic cells that are S-100 and neuron specific enolase positively stained. They are mostly located in the oral cavity and skin. GCTs are not common in the gastrointestinal tract, where the most common location is the esophagus. These tumors are usually seen in the 4th and 6th decade of life and are rare in children. To our knowledge, only one case report exists regarding the endoscopic resection of a cecal GCT in a child. Herein, we report an endoscopic resection of a colonic GCT in a child.